Contextualizing phenomenology in event management research. Issue 1 (2014) - Vassilios Ziakas; Nikolaos Boukas
<x xml:space="preserve"> Abstract </x> Purpose – Although the core phenomenon of events is the experiences and the meanings attached to them, there is limited management research on the experiential, existential and ontological dimensions of events. Phenomenology provides a sound philosophical framework for studying the multifaceted dimensions of experiences and associated meanings of events. However, quite surprisingly, phenomenology has not yet been systematically applied on the event management field. The purpose of this conceptual paper is to introduce phenomenology to the study of events, demonstrate its value for the field and encourage as well as guide its application on event management research. Design/methodology/approach – A review and synthesis of the main phenomenological streams of thought was undertaken in order to develop a research paradigm for the application of phenomenology on the event management field. Findings – The paper explains why phenomenology is needed in the study of events and their management, its conceptual underpinnings and streams of thought and finally suggests a research framework for conducting phenomenological studies in event management. Research limitations/implications – The consequences of the phenomenological perspective are delineated for explaining how the study of event meanings and experiences can be undertaken from this perspective. The limitations of phenomenology are noted such as the emphasis on "lifeworld" subjectivity and subsequent difficulty to claim the generalizability of research findings. Practical implications – The suggested research framework can guide future event management research on how to apply phenomenology to the study of event experiences and meanings. On this basis, practitioners can get insight regarding how to develop and design events that optimize the perceived experiences of attendees. Originality/value – While the experiential paradigm and the phenomenological turn have been spread across many disciplines emphasizing the essence of lived experiences in a variety of human interactions and exchanges, the event management field lags behind. This is unfortunate and has to be addressed as the experiences and meanings shape the essence of events. Therefore, this conceptual paper hopes to inspire, encourage and guide event management researchers to embrace and apply the phenomenological perspective on their future research endeavors, which can profitably complement and expand the predominant research paradigms in the field.